AN ANALYSIS OF POSITIVE POLITENESS STRATEGY IN MOANA MOVIE - Lorentia Fredika Warouw; Nurmin Samola; Maikel Sanger (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The study, "An Study Of Positive Politeness Technique In Moana Movie," focuses on politeness in relation to Brown and Levinson's positive politeness approach. This study was undertaken with the intention of describing the effective politeness technique used in the Moana movie. In this study, the descriptive qualitative method was used. The conversations in the Moana movie script served as the source of the data for this investigation. The analysis of the data revealed three effective politeness strategies in the film Moana. The statistics are as follows: 13 pique the listener's interest more, 4 exaggerate, and 4 make promises or offers. Also, the most commonly employed tactic in Moana's film is to heighten listener interest because she is the primary character